Reliable Patterning, Transfer Printing and Post‐Assembly of Multiscale Adhesion‐Free Metallic Structures for Nanogap Device Applications. (22nd June 2020) - Chen, Yiqin; Shu, Zhiwen; Feng, Zhanyong; Kong, Ling'an; Liu, Yuan; Duan, Huigao
Abstract: Patterning of metallic nanogaps with ultrasmall gap size on arbitrary substrates is of great importance for various applications in nanoelectronics, nanoplasmonics, and flexible optoelectronics. Common lithographic approaches suffer from limited resolution in defining ultrasmall nanogaps and restrictive available substrates for flexible and stretchable devices. In this work, a process portfolio to overcome the above limitations is proposed, enabling the fabrication of multiscale metallic nanogaps with reduced gap size on specific substrates for functional devices. The portfolio combines the recently developed sketch and peel lithography strategy, nanotransfer printing, and post‐mechanical assembly. Among the portfolio, the sketch and peel lithography strategy provides the unique capability to rapidly and reliably define multiscale adhesion‐free metallic nanostructures and nanogaps, which significantly facilitates the subsequent transfer printing process. Nanoplasmonic and nanoelectronic devices with ultrasmall nanogaps that are inaccessible with existing patterning approaches are fabricated to demonstrate the applicability of this fabrication strategy. The portfolio could also have potential for a variety of other applications in flexible and stretchable optics, electronics, and optoelectronics. Abstract : This work proposes a process portfolio to overcome the limitations in the high‐resolution multiscale patterning of metallic nanogaps with ultrasmall size on arbitrary substrates. This fabrication strategy enables one to reduce the nanogap size in nanoplasmonic and nanoelectronic devices to the dimension that are inaccessible with existing patterning approaches.